Fatigue design of selected details in steel bridges. (October 2019) - Kuhlmann, U.; Bove, S.; Breunig, S.; Drebenstedt, K.
Abstract: Highway and railway bridges are exposed to cyclic stressing due to traffic loads and, therefore, have to be evaluated concerning fatigue. In most cases the fatigue evaluation is performed according to Eurocode 3 Part 1–9 on nominal stresses. To apply this nominal stress approach a detail catalogue is required classifying all relevant constructional details in terms of fatigue. Unfortunately, the existing detail catalogue of Eurocode 3 Part 1–9 reflects the state of the art of the 1990s and misses constructional details being important for today's bridge design. As an example the derivation of a new detail, the so-called lamellae joint, is presented. Furthermore, for two new types of innovative steel bridges, where Eurocode 3 Part 1–9 does not yet specify rules able to evaluate the characteristics of these bridges, research results are shown. These are the thick-plate trough bridges and truss bridges made of thick-walled circular hollow sections (CHS). The paper starts with an overview on the recent Eurocode developments, addressing more specific the fatigue verification according to EN 1993-1-9 and the statistical analysis of fatigue test data. In the following, information is given on the outcome of some recent research projects striving to extend the application range of Eurocode 3 Part 1–9. The final conclusion, in spite of all differences, shows a common tendency. Highlights: The lamellae joint has at least the same characteristic fatigue strength as the detail "Transverse butt welds". In trough bridges the main failure is caused by the global longitudinal bending of the main girder. In trough bridges the observed multiaxial stress state should be considered for fatigue design using principal stresses. The fatigue strength of welded CHS K-joints with thick-walled chords is comparable to that of thin-walled tubular joints. In all considered bridge structures and all investigated constructional details a pronounced size effect could be observed.